Two variants of bonded parallel insertion systems and their generative power - Yosman, Ahmad Firdaus; Holzer, Marcus; Truthe, Bianca; Fong, Wan Heng; Sherzod Turaev, Sherzod (UTM, 2016)
Insertion is an operation in formal language theory that generalizes the operation of concatenation of words in a language, where its variants allow words to be added into any place in another word in different ways. Parallel insertion is a variant of insertion that simultaneously adds words between all letters of a word and also at the right and left extremities. In previous research, restrictions have been imposed on the rules of the operation of insertion to introduce a new variant, called bonded insertion systems, which include bonded sequential and parallel insertions. Motivated by the atomic behavior of chemical compounds in the process of chemical bonding, the generative power of bonded insertion systems has been investigated where a language hierarchy was obtained. In this paper, we introduce new variants of bonded parallel insertion systems, namely bonded Indian parallel insertion systems and bonded uniformly parallel insertion systems. Here, some results regarding the generative power of these new systems are presented and a language hierarchy is constructed.